EFFECTS OF ARTIFICIAL BEACH NOURISHMENT ON WATER QUALITY AND MARINE BIOTA: A CRITICAL REVIEW: Efeitos das obras de engorda artificial de praias na qualidade da água e na biota marinha: Uma revisão crítica - Nunes da Silva, Luiz Carlos; Barbosa Viana, Michael (Arquivos de Ciências do Mar, 2024)
The aim of this paper is to provide an overview of the main effects of beach nourishment on water quality and marine biota through a critical review of the literature, considering the main scientific publications of the last twenty-five years. In the research conducted, artificial beach nourishment has proven to be an efficient means of combating the process of coastal erosion, and most of this research has focused on beaches on the European continent and in the USA. Following the completion of the fattening works, the main impacts observed were increased water turbidity, the presence of bacteria indicative of fecal contamination in the sediment of the fattening area, changes in the composition of the benthic community and the disappearance of Posidonia oceanica meadows. Most of these effects were temporary and some of them had a recovery time of up to four years. Finally, it is suggested to improve monitoring programs for the impacts of artificial beach fattening, as the lack of management and planning by the parties involved in fattening works may contribute to increase these impacts on the marine ecosystem. Keywords: Dredging, environmental impact, beach fattening work